2000
DOI: 10.1086/308947
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Photometric Redshift Estimation

Abstract: Photometric redshift estimation is becoming an increasingly important technique, although the currently existing methods present several shortcomings which hinder their application. Here it is shown that most of those drawbacks are efficiently eliminated when Bayesian probability is consistently applied to this problem. The use of prior probabilities and Bayesian marginalization allows the inclusion of valuable information, e.g. the redshift distributions or the galaxy type mix, which is often ignored by other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
1,458
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,206 publications
(1,475 citation statements)
references
References 40 publications
13
1,458
1
3
Order By: Relevance
“…The photometric redshifts obtained for this survey have been calculated with BPZ2.0 (Benitez in prep), an improved version of BPZ (Benítez 2000) capable of also providing stellar masses. The catalogues, including a full range of measured properties of the galaxies, are publicly available 3 (see Molino et al 2014 for details).…”
Section: The Alhambra Surveymentioning
confidence: 99%
“…The photometric redshifts obtained for this survey have been calculated with BPZ2.0 (Benitez in prep), an improved version of BPZ (Benítez 2000) capable of also providing stellar masses. The catalogues, including a full range of measured properties of the galaxies, are publicly available 3 (see Molino et al 2014 for details).…”
Section: The Alhambra Surveymentioning
confidence: 99%
“…Our photometric redshift estimates are made with two different techniques: Le Phare (LPZ) 15 and Bayesian Photometric Redshifts (BPZ) 16 . LPZ photometric redshifts are based on a template fitting procedure with a maximum likelihood (χ 2 ) estimate.…”
mentioning
confidence: 99%
“…This will be done using the Bayesian approach implemented in BPZ (Benítez 2000), updated in BPZ2.0. It has been shown that the analysis of the residuals of the photo-z procedure in the different bands can help to detect offsets in the original photometry, that applied to all the objects can improve the final photometric redshifts (Molino et al 2014).…”
Section: Challenge 6 Photometric Redshiftmentioning
confidence: 99%